Symbiotic effectiveness of Bradyrhizobium strains on soybean growth and productivity in Northern Mozambique - Kyei-Boahen, Stephen; Savala, Canon Engoke Norris; Muananamuale, Carlos Pedro; Malita, Carlos; Wiredu, Alexander Nimo; Chibeba, Amaral Machaculeha; Elia, Patrick; Chikoye, David (Frontiers in Sustainable Food Systems, 2023)
Inoculation of soybean [Glycine max (L.) Merr.] with rhizobia strains is a low-cost investment which can increase yields of smallholder farmers in Mozambique. We evaluated the performance of four Bradyrhizobium strains to identify the best strain for the major soybean producing agro-ecologies. Field experiments were conducted in three ecologies in 2018 and 2019 using soybean variety Zamboane and four inoculant strains in a randomized complete block design with four replications. Treatments consisted of strain USDA 110, USDA 136, USDA 442, WB74 and a non-inoculated control. The indigenous rhizobia populations at the sites were estimated using the most probable number (MPN) technique. The results indicated that the population ranged from 9.0 x 101 to 2.2 x 103 cells g-1 soil. All four strains increased nodulation but USDA 110 was superior at two sites that had low resident rhizobia population, whereas USDA 442 and WB74 were the best at the site which contained relatively high native rhizobia population. On average, the strains tripled the number of nodules and increased the dry weight up to 5.8-fold. Inoculation increased shoot dry weight and N content at podding, plant biomass, and number of pods plant-1 across sites but the effects of the strains on seeds per pod, and 100-seed weight were inconsistent. Shoot N content did not differ among the strains and ranged from 15.70 g kg-1 for the control to 38.53 g kg-1 for plants inoculated with WB74. All four strains increased soybean grain yield across sites in 2018 but USDA 110 outperformed the other strains and was also the best at one of the two sites in 2019. Grain yield responses associated with USDA 110 ranged from 552 kg ha-1 (56%) to 1,255 kg ha-1 (76%). Positive correlations between nodule dry weight plant-1 and seed yield, and number of pods plant-1 and grain yield occurred. On average, inoculation increased net returns by 182.57-395.35 ha-1 over that for the non-inoculated control in 2018 but drought stress in 2019 reduced the benefit. The results demonstrate that USDA 110 was the best inoculant strain and has the potential of increasing smallholder productivity and net returns.